2003
DOI: 10.1016/s0013-9351(02)00003-8
|View full text |Cite
|
Sign up to set email alerts
|

The Comet assay for the detection of DNA damage in Mus spretus from Doñana National Park

Abstract: Doñana Park (Spain), a protected area in Europe, was affected by an environmental disaster in April 1998 that caused the spreading of acidic water and mud full of toxic metals from the Aznalcollar pyrite mine. In order to assess the contamination in the area and to monitor the possible biological effects of the toxic spill, a series of coordinated studies was performed utilizing several animal species living in that area. We performed genotoxicity monitoring using the Comet assay on peripheral blood leukocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Miscellaneous.-Recently, Mus spretus has been established as a suitable bioindicator of genetic risk induced by environmental pollution in natural areas (Ieradi et al 1998;Nunes et al 2001b) or those affected by environmental disasters (Festa et al 2003;Ruíz-Laguna et al 2001;Tanzarella et al 2001). The adverse effects of heavy metals (mostly chromium, manganese, iron, copper, zinc, and selenium) were appraised by Nunes et al (2001a), who compared the fluctuating asymmetry of dental (molar) characteristics and confirmed that tooth size was reduced in the contaminated area, and that developmental instability increased in relation to stress, even when contamination levels were low.…”
Section: Ecologymentioning
confidence: 99%
“…Miscellaneous.-Recently, Mus spretus has been established as a suitable bioindicator of genetic risk induced by environmental pollution in natural areas (Ieradi et al 1998;Nunes et al 2001b) or those affected by environmental disasters (Festa et al 2003;Ruíz-Laguna et al 2001;Tanzarella et al 2001). The adverse effects of heavy metals (mostly chromium, manganese, iron, copper, zinc, and selenium) were appraised by Nunes et al (2001a), who compared the fluctuating asymmetry of dental (molar) characteristics and confirmed that tooth size was reduced in the contaminated area, and that developmental instability increased in relation to stress, even when contamination levels were low.…”
Section: Ecologymentioning
confidence: 99%
“…The alkaline Comet assay was performed as described by Festa et al (2003). Twenty microliters of whole blood were mixed in 180 μl of 0.7% low melting point agarose in PBS (Ca and Mg free) at 37°C, and immediately pipetted onto a frosted glass microscope slide precoated with a layer of 1% normal melting point agarose, similarly prepared in phosphate-buffered saline (PBS).…”
Section: Standard Comet Assaymentioning
confidence: 99%
“…A total of 23 male adult M. spretus were collected in October 1999 in four locations of the Park (Tanzarella et al, 2001;Festa et al, 2003). The first one, near Aznalcazar village (AZN), was located 25 km South of the broken tailings dam and had been covered by toxic sludge, whereas the second one, Cangrejo Grande (CG), was close to the reservoir of the contaminated water, which formed after the water retaining wall was built.…”
Section: Organisms Analysed and Sampling Areasmentioning
confidence: 99%
“…Following Aznalcollar disaster, toxic metals as Cd, Pb, Hg, Cu, and others were reversed in the rivers near Doñana Park and increased in the environment (Pain et al, 1998;Alzaga et al, 1999) and in the organs of Mus spretus (Cristaldi et al, in press). Previous studies (using CREST staining analysis) indicated a cytogenetic damage in mice collected near Aznalcollar mine, suggesting that animals had been exposed to aneugenic substances (Festa et al, 2003;Cristaldi et al, in press). Moreover the alteration of some biochemical biomarkers in the liver of these animals (Ruiz-Laguna et al, 2001) and modifications of the protein expression profile in the gills of S. plana clams (RomeroRuiz et al, 2006) were observed.…”
Section: Introductionmentioning
confidence: 99%